2005
DOI: 10.1182/blood-2004-12-4649
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant mitochondrial iron distribution and maturation arrest characterize early erythroid precursors in low-risk myelodysplastic syndromes

Abstract: IntroductionThe low-risk myelodysplastic syndromes (MDSs) refractory anemia (RA) and RA with ringed sideroblasts (RARS) are characterized by profound anemia and transfusion dependency, and a relatively low risk of progression to acute myeloid leukemia. 1,2 In RARS, the anemia is mirrored by hyperplastic but severely ineffective erythropoiesis due to increased apoptosis of erythroid progenitors. 3 The erythropoiesis of RA patients is also inadequate with apoptotic features, but may range from hypo-to hyperplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 39 publications
(46 reference statements)
5
91
0
1
Order By: Relevance
“…It is well recognized that there is a higher bone marrow apoptotic index in the bone marrow of low-risk MDS patients compared with high-risk MDS and MDS-AML. [38][39][40] Advanced MDS is characterized by high levels of genomic instability with a concomitant increase in cytogenetic abnormalities in comparison with early MDS. DNA damage facilitates activation of the DNA damage response (DDR) and DNA damage checkpoint pathways, which can then lead to cell cycle arrest, apoptosis, repair or cell senescence.…”
Section: Deregulated Pathways In Myelodysplastic Syndromes a Pellagatmentioning
confidence: 99%
“…It is well recognized that there is a higher bone marrow apoptotic index in the bone marrow of low-risk MDS patients compared with high-risk MDS and MDS-AML. [38][39][40] Advanced MDS is characterized by high levels of genomic instability with a concomitant increase in cytogenetic abnormalities in comparison with early MDS. DNA damage facilitates activation of the DNA damage response (DDR) and DNA damage checkpoint pathways, which can then lead to cell cycle arrest, apoptosis, repair or cell senescence.…”
Section: Deregulated Pathways In Myelodysplastic Syndromes a Pellagatmentioning
confidence: 99%
“…Although there is extensive evidence implicating abnormal expression of genes involved in heme biosynthesis, iron processing and altered mitochondrial function in the pathogenesis of RARS, none have been translated to targeted and improved therapies for these diseases. 15,16 It is possible that the role of the spliceosome in RARS and related diseases is not restricted to SF3B1, and may involve other components of the splicing machinery. This prompted us to also perform genomic sequencing of two other spliceosome components associated with SF3B1: SF3B14 and SF3B4.…”
mentioning
confidence: 99%
“…Moreover, the autophagic vacuoles were not only present in mature, but also in immature erythroblasts, indicating that mitochondrial autophagy in MDS is more pronounced and occurs earlier in the differentiation program. A recent study of Tehranchi et al 3 demonstrated that MDS CD34 þ cells have an enhanced expression of genes encoding for the erythroid lineage. Intrinsic defects in the programming of erythroid differentiation might be responsible for the early initiation of the autophagic process.…”
Section: Discussionmentioning
confidence: 99%
“…These events might be initiated by mitochondrial dysfunction owing to accumulation of reactive oxygen species (ROS) resulting from aberrant iron mitochondrial distribution in ringed sideroblasts. 3 Loss of mitochondrial transmembrane potential can also induce autophagy, a natural degradative process in which cytoplasmic material, including organelles and macromolecules, is segregated into double-membraned vesicles (autophagosomes), which are subsequently degraded in a lysosomal dependent manner. 4 During terminal differentiation erythroid cells undergo enucleation and removal of organelles.…”
Section: Introductionmentioning
confidence: 99%